Partisipasi Masyarakat Dalam Program Keluarga Berencana (KB ) Intra Uterine Device (IUD) Di Desa Murung Raya, Balah Paikat Dan Hakurung Kecamatan Daha Utara Kabupaten Hulu Sungai Selatan - Siti Raudah; Marzuki (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: Community participation is the main requirement in achieving an expected activity goal. In fact, community participation in the Intra Uterine Device (IUD) Family Planning program in the villages of Murung Raya, Balah Paikat and Hakurung is still low. According to data from the 2022 Family Planning Counseling Center, people who use IUD KB in Murung Raya Village (2 people), Balah Paikat (0 people) and Hakurung (0 people). People still use a lot of birth control injections and birth control pills. There are people who are pregnant and want to have children. The community does not understand about this IUD family planning because they have never participated in socialization. This study aims to determine community participation in the Intra Uterine Device (IUD) family planning program in the villages of Murung Raya, Balah Paikat and Hakurung. And the factors that influence community participation in the Intra Uterine Device (IUD) family planning program. This type of research is descriptive qualitative. The data source of the informant withdrawal technique used purposive sampling of 15 informants. Data collection techniques were carried out by interviews, observation, and documentation. Analyzed with data techniques, namely data reduction, data presentation, and drawing conclusions. Credibility tests, namely extending observations, increasing persistence, triangulation, analyzing negative cases, using reference materials and conducting member checks. The results of this study indicate that community participation in the Intra Uterine Device (IUD) family planning program in the villages of Murung Raya, Balah Paikat and Hakurung is not good, it can be seen that the community still lacks information due to limited information media, many people are afraid to use IUD KB because of the issues circulating, the community does not provide ideas and ideas about the development of IUD KB, regarding achieving appropriate targets but the community uses a lot of KB injections, pills and implants. The driving factor for community participation is socialization and the installation of KB IUDs. The inhibiting factor is the lack of public knowledge and the community feeling safe using other contraceptives. To increase community participation by providing more socialization and continuing to offer this IUD KB and slowly eliminating issues circulating in the community so that people in Murung Raya Village, Balah Paikat, Hakurung and all villages in Daha Utara District want to use this IUD KB Keywords: Community Participation, Program, IUD